WE NEED TO TALK ABOUT DEFENCE : Reforming Contemporary Defence Management - Curtis, Andrew R. (Bloomsbury Academic, 2024)
"From a senior-ranking RAF Air Commodore, this is a challenging and provocative look at why the current management of Defence is failing. From past reforms, present practises and ongoing developments in the character of conflict, Curtis outlines the critical reforms needed for the UK's armed forces to fight and win in the future"--